2023
DOI: 10.1002/smtd.202201694
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Chemical Stability of MXene Through Synergy of Hydrogen Bond and Coordination Bond in Aqueous Solution

Abstract: MXenes with unique physicochemical properties have shown substantial potential in electromagnetic interference (EMI) shielding. However, the chemical instability and mechanical fragility of MXenes has become a major hurdle for their application. Abundant strategies have been dedicated to improving the oxidation stability of colloidal solution or mechanical properties of films, which always come at the expense of electrical conductivity and chemical compatibility. Here, hydrogen bond (H‐bond) and coordination b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…It can be observed that the peaks in the XPS survey spectra of MXenes and SA-MXene are essentially identical, both containing C 1s, Ti 2p, O 1s, and F 1s peaks. 52 Notably, a distinct Na 1s peak (∼1080 eV) can only be observed in the spectrum of SA-MXene due to the modification by SA. The C 1s XPS spectrum of pristine MXenes is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the peaks in the XPS survey spectra of MXenes and SA-MXene are essentially identical, both containing C 1s, Ti 2p, O 1s, and F 1s peaks. 52 Notably, a distinct Na 1s peak (∼1080 eV) can only be observed in the spectrum of SA-MXene due to the modification by SA. The C 1s XPS spectrum of pristine MXenes is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The existing polymer or metal oxide materials created tens of μF cm –2 , , and it still stands a chance of accelerating a leap in sensitivity through utilizing 2D nanosheet electrodes with the characteristics of high conductivity and specific surface area . As a recently promising nanosheet material with superhigh conductivity, the abundant surface terminal groups of MXene (Ti 3 C 2 T x ) ensure a sufficient amount of interfacial reaction. , Unfortunately, the MXene nanosheets are liable to self-restacking due to the hydrogen bond and van der Waals interactions, followed by a reduction of active surface sites contacted with ions of the dielectric layer. , On the other hand, MXene is prone to be oxidized into TiO 2 under hydrothermal and aqueous environments, which could significantly sacrifice conductivity and long-term stability. , In summary, although MXene has been identified as a functional material with extremely high surface activity, the above properties limit its direct application to highly sensitive underwater sensing for long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 On the other hand, MXene is prone to be oxidized into TiO 2 under hydrothermal and aqueous environments, which could significantly sacrifice conductivity and long-term stability. 34,35 In summary, although MXene has been identified as a functional material with extremely high surface activity, the above properties limit its direct application to highly sensitive underwater sensing for long periods of time.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Specifically, Ti 3 C 2 T x MXene etched by LiF/HCl is terminated with abundant hydrophilic groups such as −F, −O, and −OH, and thus the Ti 3 C 2 T x nanosheets disperse well in water. 22 When IL such as [C 2 VIm]Br was introduced into the Ti 3 C 2 T x suspension, it could be used as cross-linking agents to induce the electrostatic assembly of negatively charged nanosheets, resulting in the formation of a stable 3D Ti 3 C 2 T x hydrogel within seconds (Movie S1). The crosslinking effect of IL caused the loss of flowability of Ti 3 C 2 T x colloidal solution, which was demonstrated by tilting the tube (Figure 1b).…”
mentioning
confidence: 99%
“…The 3D porous aerogel architecture was fabricated through IL-induced gelation of Ti 3 C 2 T x colloidal solution (IL-Ti 3 C 2 T x ), followed by freeze-drying, as schematically shown in Figure a. Specifically, Ti 3 C 2 T x MXene etched by LiF/HCl is terminated with abundant hydrophilic groups such as −F, −O, and −OH, and thus the Ti 3 C 2 T x nanosheets disperse well in water . When IL such as [C 2 VIm]Br was introduced into the Ti 3 C 2 T x suspension, it could be used as cross-linking agents to induce the electrostatic assembly of negatively charged nanosheets, resulting in the formation of a stable 3D Ti 3 C 2 T x hydrogel within seconds (Movie S1).…”
mentioning
confidence: 99%